1988
DOI: 10.1007/bf02623607
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two glutamine-containing dipeptides on growth of mammalian cells

Abstract: The instability of the amino acid glutamine prompted us to investigate substitute compounds appropriate for culture conditions. The effect of two glutamine-containing dipeptides, alanylglutamine (Ala-Gln) and glycylglutamine (Gly-Gln), on the growth behavior of a hematopoietic cell line in culture (K562) was investigated. Growth rates and [3H]thymidine incorporation rates of cells cultivated in sterile-filtrated media, containing glutamine (Gln) or Ala-Gln or Gly-Gln, were not statistically different. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…It has been known for decades that glutamine readily breaks down into ammonium and can negatively affect cell lines and embryos (33,38). Both G-TL and G-1/G-2 contain alanyl-glutamine, a stable peptide version of glutamine that was first used as a heat-stable version of glutamine for autoclaved media (39). There was a…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for decades that glutamine readily breaks down into ammonium and can negatively affect cell lines and embryos (33,38). Both G-TL and G-1/G-2 contain alanyl-glutamine, a stable peptide version of glutamine that was first used as a heat-stable version of glutamine for autoclaved media (39). There was a…”
Section: Discussionmentioning
confidence: 99%
“…Both glutamine-containing dipeptides and glutamate have been used as substitutes for glutamine. Alanyl-glutamine (ala-gln) and glycyl-glutamine (gly-gln) can replace glutamine in animal cell culture (Roth et al, 1988;Minamoto et al, 1991;Holmlund et al, 1992;Christie and Butler, 1994). However, hydrolysis by a cellular peptidase can result in the release of high levels of glutamine into the medium (Christie and Butler, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…8 Dipeptides such as L-alanyl-L-glutamine (AlaGln) and L-glycyl-Lglutamine (GlyGln) are stable in solution and are suitable as a source of glutamine. 9 Glutamine-containing dipeptides such as AlaGln and GlyGln have also been considered as a replacement for glutamine in culture 10 and the addition of these dipeptides might achieve higher rates of embryo development in the mouse. Biggers et al 11 reported that the addition of the dipeptides AlaGln and GlyGln can play an important role in in vitro preimplantation in mouse embryos.…”
Section: Introductionmentioning
confidence: 99%